Pengaruh Pemahaman Zakat dan Lingkungan sosial terhadap Kesadaran Membayar Zakat Pada Make Up Artist di Kecamatan Tulangan, Sidoarjo - Lian Fuad; Nanda Trisnawang Anggelista (Universitas Islam Negeri Sunan Ampel Sunan Ampel, 2022)
The purpose of this study was to prove the influence of understanding of zakat and the level of religiosity on awareness of paying zakat on make up artists in the district of Tulangan Sidoarjo. In this study, the population was 34. The population in this study were Make up Artist Services (MUA) in the District of Tulangan Sidoarjo. The sampling technique in this study was using the slovin technique. Based on the total population, the total sample is 25 respondents, but only 19 respondents data can be processed. The results of this study can be concluded as follows: Understanding of Zakat and Social Environment has a significant positive effect on Awareness of Paying Zakat on Make up Artists in the Sidoarjo Region.